Aqueous extract of cornsilk confers mild diuretic activity in normal rats - Solihah, M.A.; Nurhanan, A.R.; Wan Amir Nizam, W.A.; Wan Rosli, W.I. (Universiti Kebangsaan Malaysia, 2015)
Cornsilk is traditionally used to treat illnesses related to kidney and as diuretic agent. The study was performed to evaluate the effectiveness of Malaysian cornsilk in elevating diuresis and their dose response relationship in normal Sprague-Dawley rat. The diuresis activity was determined by administered the rats with different dose treatments of 400, 500, 600, 700 and 800 mg/kg. Cumulative urine was significantly increased with the dosage levels (400-600 mg/kg) ranging from 14.06 - 20.13 mL. Cumulative urine of aqueous extract of cornsilk (AEC) at 400 mg/kg (14.06 mL) and 500 mg/kg (15.21 mL) treatments found to be significantly lower than positive control (21.25 mL). In addition, Na+ content was significantly higher compared with negative control at dosages of 500, 600, 700 and 800 mg/kg. At any rate, K+ and Cl- content of all AEC treatments were not significantly different during 24 h monitoring. The pH values were increased paralleled with the increment of AEC dosages, though it was not significant. On the other result, the ED50 of AEC was observed at 454.10 mg/kg. Malaysian AEC had shown a mild diuretic activity in elevating urine and Na+ content at dosages from 500 to 800 mg/kg. Whilst, AEC also showed an effect of potassium sparing diuretics. Thus, it is suggested that Malaysian cornsilk can be used as an alternative natural diuretic agent.